2016
DOI: 10.1039/c5nr06804e
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane delivery of anticancer drugs through self-assembly of cyclic peptide nanotubes

Abstract: Breaking the natural barriers of cell membranes achieves fast entry of therapeutics, which leads to enhanced efficacy and helps overcome multiple drug resistance. Herein, transmembrane delivery of a series of small molecule anticancer drugs was achieved by the construction of artificial transmembrane nanochannels formed by self-assembly of cyclic peptide (cyclo[Gln-(d-Leu-Trp)4-d-Leu], CP) nanotubes (CPNTs) in the lipid bilayers. Our in vitro study in liposomes indicated that the transport of molecules with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…Self-assembly of cyclic peptide ( cyclo [Gln-(D-Leu-Trp) 4 -D-Leu], CP) forms artificial transmembrane nanochannels on the cell membrane for the permeation of anti-cancer drugs, which are smaller than 1 nm. The in vivo study with these nanochannels in a grafted solid tumor model in mice showed that tumor growth was greatly inhibited by the combination of anti-cancer drugs with the cyclic peptide nanochannels [92]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Self-assembly of cyclic peptide ( cyclo [Gln-(D-Leu-Trp) 4 -D-Leu], CP) forms artificial transmembrane nanochannels on the cell membrane for the permeation of anti-cancer drugs, which are smaller than 1 nm. The in vivo study with these nanochannels in a grafted solid tumor model in mice showed that tumor growth was greatly inhibited by the combination of anti-cancer drugs with the cyclic peptide nanochannels [92]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Chen et al explored the viability of self‐organizing cyclic l , d ‐α‐peptides to carry small molecular anticancer drugs through the artificial channels they form across the cell membranes. A hydrophobic cyclic l , d ‐α‐decapeptide was designed with an inner pore suitable to complex selectively hydrophilic molecules with a smaller size than 1 nm, such as the anticancer drug 5‐fluoracyl.…”
Section: Applications Of Cyclic Ld‐peptides To Biomedicinementioning
confidence: 99%
“…In contrast, the development of novel systems for drug delivery and gene transfection appears more sound since it is based on the well‐proved propensity of cyclic l , d ‐α‐peptides to interact with cells by forming trans‐membrane channels. Applications of linear l , d ‐α‐peptides in this fields could also be envisioned since the ability of these peptides to self‐assemble in long rod‐like aggregates and to act as ion channels in bilayer membranes were shown …”
Section: Summary and Future Applicationsmentioning
confidence: 99%
“…Thus, Fluorescence imaging can be employed to understand the interactions of peptides with various enzymes 21 . The in vivo study with these nano channels in a grafted solid tumor model in mice showed that tumor growth was greatly inhibited by the combination of anti-cancer drugs with the cyclic peptide nano channels 22 .…”
Section: Self-assembling Peptide For Diagnosismentioning
confidence: 99%